2020
DOI: 10.21203/rs.3.rs-18620/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Alanine Aminotransferase in Adults with Severe and Complicated Obesity during a Milk-Based Meal Replacement Programme

Abstract: Introduction: Excess adiposity is associated with fat accumulation within the liver, and non-alcoholic steatohepatitis (NASH) is highly prevalent in bariatric patients. Elevated alanine aminotransferase (ALT) is associated with prevalent NASH. We sought to determine the influence of a milk-based meal replacement weight-loss programme on ALT levels in adults with severe and complicated obesity.Methods: We conducted a retrospective cohort study of patients who completed a 24-week meal replacement programme, c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It was previously established that metabolic syndrome and obesity were associated with elevated liver enzymes, particularly high serum ALT activity. Besides, almost 50% of obese people had elevated ALT levels in addition to NAFLD [24,25]. In the same vein, Milić et al conducted a large study on 799 obese patients and concluded that the median ALT and AST levels increased with the obesity class, exceeding the normal limits in 21% of the patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously established that metabolic syndrome and obesity were associated with elevated liver enzymes, particularly high serum ALT activity. Besides, almost 50% of obese people had elevated ALT levels in addition to NAFLD [24,25]. In the same vein, Milić et al conducted a large study on 799 obese patients and concluded that the median ALT and AST levels increased with the obesity class, exceeding the normal limits in 21% of the patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased levels of liver parameters (AST and ALT) were noted in our trials; however, there were no concerning cases in participants in the trials, and no clear evidence of hepatocellular injury. Other studies suggest that some liver enzymes may transiently increase during a dietary-induced weight loss [51, 52]. In one study, this effect varied according to sex [22]; however, overall, the effect is considered to be due to a transient deterioration in hepatic steatosis prior to improvement and, therefore, a benign effect [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that some liver enzymes may transiently increase during a dietary-induced weight loss [51, 52]. In one study, this effect varied according to sex [22]; however, overall, the effect is considered to be due to a transient deterioration in hepatic steatosis prior to improvement and, therefore, a benign effect [51, 52]. In contrast, a previous phase 2 trial with semaglutide in participants with obesity showed decreases in liver enzymes (ALT) and CRP [53].…”
Section: Discussionmentioning
confidence: 99%